Development of Robotic Rover: A review - Nurul Aqilah, Herman; Roshahliza, M. Ramli; Mohd Azrul Hisham, Mohd Adib; Mirta, Widia (IOP Publishing Ltd, 2019)
The robotic rover is defined as a small vehicle that can move over rough ground and it is initially used by NASA for space exploration. However, this type of rover is expensive, using complicated and complex materials and software as well as large in size. Robotic rover fills the gap without endangering personnel involves in life-threatening condition or scenario that human sometimes needs to deal with. It can be considered to be deployed in assisting safetyauthorities to collect information and insights as well as work lift in search and rescue operations. In this paper, the progress that has been made towards the development of robotic rover which has been done in previous years are reviewed, including the design, functions, specifications, and applications, to meet requirements in performing a variety of tasks including hazardous identification, site surveillance and monitoring. Subsequent to this, a few analyses on the design and development of the proposed robotic rover are also discussed. The ultimate aim is to come out with such rover that is portable, small in size and low cost, together with user-friendly functions and specifications for future potential applications.